MIGA Annual Report 2013 : Insuring Investments, Ensuring Opportunities - Multilateral Investment Guarantee Agency (Washington, DC: World Bank Group, 2013)
In fiscal year 2013, Multilateral Investment Guarantee Agency (MIGA) issued 2.8 billion dollars in investment guarantees for projects in our developing member countries. At 1.5 billion dollars, representing more than half of new business, the bulk of MIGA's guarantees issued support investments in Sub-Saharan Africa. Sixty-nine percent of new business volume this year was in complex projects in infrastructure and extractive industries, a strategic priority for the Agency. This year, 82 percent of MIGA's new volume fell into one or more of strategic priority areas: investments in the world's poorest countries, "South-South" investments, investments in conflict-affected countries, and investments in complex projects. MIGA also established the conflict-affected and fragile economies facility to further deepen support to this priority area.